PENGARUH MEDIA SOSIAL TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN KONSUMEN: ANALISIS BIBLIOMETRIK - Budiyanto, Arief; Pamungkas, Ibrahim Bali; Praditya, Alvin (Jurnal Ekonomi Manajemen, 2022)
This study describes how the development of research on buying interest and purchasing decisions on social media, ranging from keywords that have a lot to do with the theme of the influence of social media on consumer behavior, and the number of publications in terms of timelines, to the trend of publications on social media research. All of them are summarized through bibliometric analysis of 73 journals that are used as references. In collecting journals, researchers use certain criteria and the sources used as references must be indexed into the SINTA (science and technology index) owned by the Ministry of Education and Culture with a SINTA limit of 2-6. It was found that Instagram is the most widely used social media research theme, and social media is widely used not only for transactions but also to be able to introduce products or services owned by marketers to potential consumers and is more directed to the branding process. The clothing and beauty products sector is the sector that is most widely discussed in the next social media research theme, which is the market and food and beverage sector.